Precarious Employment during the COVID-19 Pandemic, Disability-Related Discrimination, and Mental Health. Issue 2 (May 2023) - Brown, Robyn Lewis; Ciciurkaite, Gabriele
Drawing on separate strands of research documenting the psychological consequences of (a) precarious employment and other challenges associated with the COVID-19 pandemic and (b) ableism, this study incorporates both into an examination of disability-based differences in the joint significance of discrimination and work precarity during the pandemic for mental health. Analyses utilizing data from a regional survey of people with and without disabilities in the Intermountain West (N = 2, 012) provide evidence that precarious employment, greater discrimination, and disability independently predict depressive symptoms. Further, in the context of greater discrimination, more precarious employment is found to have greater significance for people with disabilities compared to those who are not currently disabled. These findings challenge us to think about how we engage in research concerning ableism and macro-level stressors, and underscore the role of power structures and positionality in shaping the psychological impact of employment challenges experienced during the pandemic.